Blau syndrome complicated by granulomatous tubulointerstitial nephritis and immune complex mediated glomerulonephritis: A case report and review of the literature - Kelly M. Garrity; Richard Chiu; Rachana Srivastava; Deborah K. McCurdy; Jonathan E. Zuckerman (Elsevier, 2024)
Blau syndrome is a rare, autosomal dominant or de novo mutation, granulomatous, auto-inflammatory disorder classically manifesting as a triad of polyarthritis, uveitis, and dermatitis. Rarely, this disease involves visceral sites such as the liver, lung, and kidney. In this report, we describe a case of a 13-year old female with Blau syndrome, with prior findings of polyarticular arthritis, uveitis, granulomatous sialadenitis of the right parotid gland, and positive NOD2 mutation testing, whose serum creatinine acutely rose despite being on anti-TNF-alpha therapy since age two. Kidney biopsy revealed granulomatous tubulointerstitial nephritis (TIN) and an immune complex (IC)-mediated glomerulonephritis attributed to Blau syndrome. We conducted a literature search to find all reported cases of Blau syndrome with biopsy findings of granulomatous renal involvement, finding ten other case reports. We assessed the likelihood of TIN and immune complex deposition, the drugs used to treat these patients, and the clinical outcomes. We found coexisting IC renal deposition rare, occurring in 2/11 patients including ours and renal involvement that was anti-TNF unresponsive was only present in our patient with a recorded renal treatment outcome.